2022
DOI: 10.1007/s10658-022-02535-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and diversity of black-foot pathogens on asymptomatic nursery-produced grapevines in Turkiye

Abstract: Black-foot (BF) disease of grapevines in nurseries and young vineyards is caused by soilborne Cylindrocarpon-like asexual morphs. They can be found both in symptomatic and asymptomatic vines, being spread to new grape growing areas during vineyard establishment. In this study, 42 grapevine nurseries located in different geographical regions in Turkiye were surveyed in 2021 to determine the presence of BF pathogens on asymptomatic marketable plants.Black-foot fungi were isolated from the roots or basal ends of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Th e results showed that dieback (in 30% of surveyed nurseries) and Petri disease pathogens (33% of nurseries) were moderately prevalent. Previously, black foot pathogens were found to be very common in most of surveyed nurseries (Akgül et al, 2022). Nine of 43 nurseries producing non-graft ed Sultana Seedless grapevines were examined in this survey, and dieback and Petri disease pathogens were identi- fied only in three nurseries, from asymptomatic plants.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Th e results showed that dieback (in 30% of surveyed nurseries) and Petri disease pathogens (33% of nurseries) were moderately prevalent. Previously, black foot pathogens were found to be very common in most of surveyed nurseries (Akgül et al, 2022). Nine of 43 nurseries producing non-graft ed Sultana Seedless grapevines were examined in this survey, and dieback and Petri disease pathogens were identi- fied only in three nurseries, from asymptomatic plants.…”
Section: Discussionmentioning
confidence: 98%
“…Akgül and Ahioğlu (2019) screened GTD pathogens associated with young grapevine decline in 1-3-year-old vineyards in Southern Türkiye. A survey 3 years later revealed occurrence and diversity of black foot pathogens in nurseries (Akgül et al, 2022). However, no substantial information is available on the current status of other GTD pathogens in marketable dormant plants in Turkish grapevine nurseries.…”
Section: Introductionmentioning
confidence: 99%
“…(Gramaje et al, 2011a) and Pleurostoma richardsiae (Halleen et al, 2007b). Up to 29 species of Cylindrocarpon-like asexual morphs belonging of Campylocarpon, Cylindrocladiella, Cylindrodendrum, Dactylonectria, Ilyonectria, Neonectria, Pleiocarpon and Thelonectria genera have been associated with black-foot of grapevine (Gramaje et al, 2018;Aigoun-Mouhous et al, 2019;Akgül et al, 2022). Dactylonectria torresensis is the most common species associated with this disease in Europe (Reis et al, 2013, Carlucci et al, 2017 and Algeria (Aigoun-Mouhous et al, 2019), while Da.…”
Section: Fungal Trunk Diseases Of Applementioning
confidence: 99%
“…Currently, more than 30 fungal species of Campylocarpon, Cylindrocladiella, Dactylonectria, Ilyonectria, Neonectria, Pleiocarpon, and Thelonectria, commonly known as Cylindrocarpon-like asexual morphs, are associated with black foot (Agustí-Brisach and Armengol, 2013;Lombard et al, 2014;Carlucci et al, 2017;Aigoun-Mouhous et al, 2019). Among these, D. torresensis has been reported as the prevalent species in several countries (Reis et al, 2013;Berlanas et al, 2017;Carlucci et al, 2017;Aigoun-Mouhous et al, 2019;Akgül et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Black foot pathogens have been frequently isolated from nursery grapevine plants, indicating that these plants play important roles in the spread of this disease (Halleen et al, 2006a;Abreo et al, 2010;Agustí-Brisach et al, 2013;Cardoso et al, 2013;Carlucci et al, 2017;Pintos et al, 2018;Aigoun-Mouhous et al, 2019;Berlanas et al, 2020;Akgül et al, 2022). Several studies have focused on determining when infection occurs during propagation processes, and there is consensus that the nursery rooting phase is where black foot pathogen infections increase significantly (Halleen et al, 2003;Agustí-Brisach et al, 2013;Carbone et al, 2022).…”
Section: Introductionmentioning
confidence: 99%